Regulators, Pivotal Clinical Trials, and Drug Regulation in the Age of COVID-19. (January 2021) - Lexchin, Joel; Graham, Janice; Herder, Matthew; Jefferson, Tom; Lemmens, Trudo
Medicine regulators rely on pivotal clinical trials to make decisions about approving a new drug, but little is known about how they judge whether pivotal trials justify the approval of new drugs. We explore this issue by looking at the positions of 3 major regulators: the European Medicines Agency, Food and Drug Administration, and Health Canada. Here we report their views and the implications of those views for the approval process. On various points, the 3 regulators are ambiguous, consistent, and demonstrate flexibility. The range of views may well reflect different regulatory cultures. Although clinical trial information from pivotal trials is becoming more available, regulators are still reluctant to provide detailed information about how that information is interpreted. As medicines and vaccines come up for approval for treatment of COVID-19, transparency in how pivotal trials are interpreted will be critical in determining how these treatments should be used.